2007
DOI: 10.1007/s11748-006-0087-1
|View full text |Cite
|
Sign up to set email alerts
|

Tetralogy of Fallot in teenagers and adults: surgical experience and follow-up

Abstract: Total correction in this subset of patients offers the best option for long-term symptom-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…All patients were in NYHA class I. Similar data were reported by Bisoi et al .,11 who stated that total correction of ToF in teenagers and adults offers the best option for long-term, symptom-free survival.…”
Section: Discussionsupporting
confidence: 84%
“…All patients were in NYHA class I. Similar data were reported by Bisoi et al .,11 who stated that total correction of ToF in teenagers and adults offers the best option for long-term, symptom-free survival.…”
Section: Discussionsupporting
confidence: 84%
“…34,40 A total of four studies reported that high scores of quality of life were positively associated with higher achievement in the educational system and higher levels of education in adolescents and young adults with CHD. 28,39,40,43…”
Section: Resultsmentioning
confidence: 99%
“…The reasons are multifactorial -the chronic effects of cyanosis, severe right ventricular dysfunction at presentation, lack of adequate myocardial protection during cardiopulmonary bypass (excessive return due to collateral circulation), and muscle resection on an ''ageing'' right ventricle. 8 Other contributing factors include renal impairment and a bleeding diathesis. In our series, severe right ventricular dysfunction and a failed modified Blalock-Taussig shunt were responsible for the deaths in the tetralogy patients.…”
Section: Mortalitymentioning
confidence: 99%